Fundamentals of accountancy, business and management : part 2 : senior high school - accountancy, business and management (ABM) specialized subject - Ferrer, Rodiel C.; Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2017)
"With times changing at an ever-faster pace, engaging in business is becoming more and more competitive. As a future business professional, you need to equip yourself with the right knowledge that will help survive in the business world."
English text.
Keywords: Business; Accounting; Management